Color Doppler Imaging of Cerebral-Umbilical Pulsatility Ratio in Intrauterine Growth Retardation - Islam, Iftadul; Yasmin, Tarana; Rubaiat, Laila; Arephin, Syed Shamsul; Hossain, Mohammad Mahbub; Asfia, Azizi (Journal of Enam Medical College, 2017)
Background: Intrauterine growth retardation (IUGR) refers to a condition in which a fetus is unable to achieve its genetically determined potential size. IUGR may also be defined as growth at the 10th or less percentile for weight of the all fetuses at that gestational age. It has long been recognized that impaired fetoplacental perfusion is associated with intrauterine growth retardation. Ultrasonography with Color Doppler has provided a new tool for this purpose. Objective: To evaluate the role of Color Doppler ultrasonography in the diagnosis of IUGR. Materials and Methods: This prospective study was carried out in the department of Radiology & Imaging of Dhaka Medical College Hospital within a period of January 2010 to September 2011 on 90 patients aged between 17?35 years who were clinically suspected as cases of IUGR or previously USG diagnosed cases of IUGR. Results: The highest incidence of IUGR was found in the age group between 21?25 years. The mean gestational age at birth was 33.2 ± 3.5 weeks and mean birth weight 1.3 ± 6.2 kg in case of abnormal cerebral-umbilical (C/U) ratio group. According to cerebral-umbilical pulsatility index (PI) value 65 cases (72.2%) were diagnosed as abnormal and 25 (27.8%) as normal flow pattern. Perinatal findings showed that 67 were small for gestational age (SGA) and 23 had normal birth weight. The validity of cerebral-umbilical PI ratio for diagnosis of IUGR was studied by calculating sensitivity, specificity, accuracy, PPV and NPV. Conclusion: In this study Color Doppler findings of cerebral-umbilical vessels and the validity tests reveal that Color Doppler evaluation of middle cerebral artery (MCA) and umbilical artery (UA) PI ratio is an useful modality in diagnosis of IUGR. J Enam Med Col 2017; 7(3): 140-145